1996
DOI: 10.1177/00957984960221006
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Achievement Performance: A Confirmation Bias

Abstract: This study expands on John Darley and Paget Gross's 1983 research examining the process leading to the confirmation of a perceiver's expectancies about a target individual when the social label that created the expectancy provides poor or tentative evidence about the target's true dispositions or capabilities. In line with previous findings, stereotype information in the no-performance condition did not produce differential estimates of the child's achievement ability, but stereotype information did affect est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Scholars find that Black and/or Latino students tend to receive lower ratings from teachers than White and Asian students across a number of dimensions, including academic ability and achievement (Ferguson, 2003; McKown and Weinstein, 2008; Murray, 1996; Oates, 2003; Ready and Wright, 2011), academic engagement and approaches to learning behaviors (Downey and Pribesh, 2004; Masten et al, 1999; McGrady and Reynolds, 2013; Pigott and Cowen, 2000), problem behaviors (Downey and Pribesh, 2004; McGrady and Reynolds, 2013; Pigott and Cowen, 2000), and physical appearance and presentation of self (Ferguson, 2000; Morris, 2005b). Scholars have also noted racial variation in teachers’ reactions to students who exhibit similar behaviors (Entwisle and Alexander, 1988; Murray, 1996; Partenio and Taylor, 1985).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Scholars find that Black and/or Latino students tend to receive lower ratings from teachers than White and Asian students across a number of dimensions, including academic ability and achievement (Ferguson, 2003; McKown and Weinstein, 2008; Murray, 1996; Oates, 2003; Ready and Wright, 2011), academic engagement and approaches to learning behaviors (Downey and Pribesh, 2004; Masten et al, 1999; McGrady and Reynolds, 2013; Pigott and Cowen, 2000), problem behaviors (Downey and Pribesh, 2004; McGrady and Reynolds, 2013; Pigott and Cowen, 2000), and physical appearance and presentation of self (Ferguson, 2000; Morris, 2005b). Scholars have also noted racial variation in teachers’ reactions to students who exhibit similar behaviors (Entwisle and Alexander, 1988; Murray, 1996; Partenio and Taylor, 1985).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Previous studies have found that teachers are less accurate in rating minority children's academic ability than the ability of Caucasian children and react differently to the same behaviors exhibited by African American and Caucasian children (Alexander et al, 1987;Murray, 1996;Partenio & Taylor, 1985). Teachers in our sample may have expected less collaborative or more strained relationships with African American parents and students.…”
Section: Racial Differences In Relational Supportsmentioning
confidence: 99%
“…SES has been examined in relation to other social categories, such as race and ethnicity (Brezina & Winder, 2003;Niemann, O'Connor, & McClorie, 1998;Weeks & Lupfer, 2004), gender (Dasgupta, 2005;Willis & Carlson, 1993), sexuality (Cortese, 1989), eating disorders (Gard & Freeman, 1996), physical disabilities (Banks & Marshall, 2005), or some combination of the above (Jussim & Eccles, 1995;Madon et al, 1998;Jussim, Eccles, & Madon, 1996;Murray, 1996;Triandis & Triandis, 1987). Lott and Saxon (2002) examined the impressions that participants' formed when rating a woman who was running for the vice president of her children's Parent Teacher Organization (PTO).…”
Section: Perceptions Of High Versus Low Ses Individualsmentioning
confidence: 99%